KUALITAS PELAYANAN WAJIB LAPOR PADA BALAI PEMASYARAKATAN KELAS II AMUNTAI KABUPATEN HULU SUNGAI UTARA - Budiman, Arif; An’Nur, M.Yusuf Kahfi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the quality of mandatory reporting services at the Class II Amuntai Correctional Center and to identify the supporting and inhibiting factors affecting its effectiveness. The research is motivated by the strategic role of correctional centers in the social reintegration process and the importance of humane and professional services. This descriptive qualitative research employed in-depth interviews and direct observation involving correctional officers and clients. The findings reveal that service quality is relatively good, especially in terms of staff professionalism, friendliness, and access to information. However, challenges such as limited human resources, inadequate infrastructure, and suboptimal waiting times remain. In conclusion, despite structural limitations, service quality is maintained due to the competence and work ethics of the officers. These findings are crucial as a basis for policy-making to improve correctional service quality in the future.